Placental Ageing in Adverse Pregnancy Outcomes: Telomere Shortening, Cell Senescence, and Mitochondrial Dysfunction. (22nd May 2019) - Manna, Samprikta; McCarthy, Cathal; McCarthy, Fergus P.
Abstract : Preeclampsia is a multisystemic pregnancy disorder and a major cause of maternal and neonatal morbidity and mortality worldwide. The exact pathophysiology of preeclampsia remains unclear; however, it is speculated that the various pathologies can be attributed to impaired vascular remodelling and elevated oxidative stress within the placenta. Oxidative stress plays a key role in cell ageing, and the persistent presence of elevated oxidative stress precipitates cellular senescence and mitochondrial dysfunction, resulting in premature ageing of the placenta. Premature ageing of the placenta is associated with placental insufficiency, which reduces the functional capacity of this critical organ and leads to abnormal pregnancy outcomes. The changes brought about by oxidative insults are irreversible and often lead to deleterious modifications in macromolecules such as lipids and proteins, DNA mutations, and alteration of mitochondrial functioning and dynamics. In this review, we have summarized the current knowledge of placental ageing in the aetiology of adverse pregnancy outcomes and discussed the hallmarks of ageing which could be potential markers for preeclampsia and fetal growth restriction.